2006
DOI: 10.1207/s15326934crj1802_4
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Planning: Training Interventions to Develop Creative Problem-Solving Skills

Abstract: Creative thought requires planning to support the refinement and successful implementation of new ideas. In this study, 174 people were given training intended to provide more effective strategies for executing two key skills held to be involved in implementation planning-penetration (e.g., identification of key causes) and forecasting. The quality and originality of the plans obtained on a transfer task, involving implementation of a new educational curriculum, were assessed. It was found that training foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 79 publications
4
75
0
2
Order By: Relevance
“…These findings are in line with research on problem solving and planning in domains such as creativity, where strategy-based training is effective in enhancing skills (e.g., Osburn and Mumford, 2006;Scott et al, 2004). Table VI presents the results of general instructional characteristic moderators.…”
Section: Business Ethicssupporting
confidence: 83%
“…These findings are in line with research on problem solving and planning in domains such as creativity, where strategy-based training is effective in enhancing skills (e.g., Osburn and Mumford, 2006;Scott et al, 2004). Table VI presents the results of general instructional characteristic moderators.…”
Section: Business Ethicssupporting
confidence: 83%
“…In a study cited as an example by these authors, it was observed that, in a briefing presentation-an exercise in which several letters with information were distributed to students-, those who received information considered to be key points or anomalies produced more creative solutions. In another study, by Osburn and Munford (2006), high-school students who received briefings related to penetration capacity and planning produced more creative outcomes. After reviewing numerous studies, the authors concluded that briefings that stimulate disruption lead to a more productive search for information.…”
Section: Tools For Dealing With Complex Problemsmentioning
confidence: 95%
“…Research into creative problem solving suggests that training in the combination of divergent and convergent thinking should lead to better outcomes than training in divergent thinking alone (Brophy 2001;Osburn and Mumford 2006). One benefit is that training in both allows auditors to avoid consistency checking, which allows them to focus on establishing a more exhaustive list of explanations.…”
Section: Hypothesis Developmentmentioning
confidence: 99%